Design of Nursing Bed Control System Based on STM32. (November 2020) - Zhang, Huimin; Sun, Hongmin; Zhang, Xianda; Guo, Xingzhao
Abstract: In order to solve the problems of low intelligence, lack of function in the domestic nursing beds, a multifunctional intelligent nursing bed for daily care in homes and nursing homes was designed. The control system adopts STM32 series chips as the control core, uses PWM modulation to simultaneously control the working state of multiple linear drivers and solenoid valves to achieve posture adjustment. The closed-loop control of the working status of the air circuit and water circuit hardware through the pressure sensor and PID adjustment algorithm realizes the function of sewage treatment. Improve the intelligence of nursing bed through the design of voice recognition and remote communication module. The application of the control system improves the convenience of operation, control intelligence and safety and reliability of nursing bed equipment.